Archetypal images of a literary fairy tale (Eurasian Journal of Philology Science and Education, 2025)
The paper is devoted to the study of archetypal images in the genre of literary fairy tales. Any author's work has a certain set of archetypal images that have their own special national meaning. Each image has its own specific functions that embody artistic, emotional, psychological, social and philosophical tasks. These tasks form the author's final vision when choosing a particular image. One of such bright and frequent images in Kazakh folklore studies is the image of a young neophyte, a boy or a girl. A boy often personified in the image of a bald - Tazsha, which has been successfully transformed into the genre of a literary fairy tale. In the same way, the images of animals, which are the first characters in fairy tales as a whole, and the analogue of their visions have often been and still are indicative. An example of the analysis was the works of Guldana Mukhtarbekkyzy Tazsha bala: kundi kaitaru (Boy Tazsha: the return of the sun), Zaure Torekhanova Amina Turan in the country of nomads and Alibek Baibol Ormandagy zhiyn (Meeting in the forest). To reveal the author's intention and function of images, the method of post-Freudian analysis, the method of cognitive literary criticism, as well as the statistical method used to identify the frequency of images are used.    Keywords: archetypal image, plot, literary fairy tale, motif, initiation, author, unconscious mind, myth.